2002
DOI: 10.1055/s-2002-26693
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Quality of Life after a Long-Term Intensive Care Stay

Abstract: Long-term treatment of critically ill patients is admittedly burdened with high in-hospital and follow-up mortality. However, the excellent physical and psychological recovery of survivors unequivocally supports the employment of all technical and personnel resources within modern intensive care medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 11 publications
4
25
0
3
Order By: Relevance
“…The other 16 studies were retrospective (Table 3). 3,7,9,[25][26][27][28][29][30][31][32][33][34][35][36][37] The retrospective studies included 1,438 patients. Two studies were prospective and included 100 patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The other 16 studies were retrospective (Table 3). 3,7,9,[25][26][27][28][29][30][31][32][33][34][35][36][37] The retrospective studies included 1,438 patients. Two studies were prospective and included 100 patients.…”
Section: Resultsmentioning
confidence: 99%
“…In 8 studies, the definition of prolonged ICU stay was >5 days. 3,26,27,29,32,33,36,37 The next most common definition was >7 days, reported in 7 studies. 4,9,25,30,31,34,36 Two studies considered ≥2 days in the ICU as prolonged.…”
Section: Definitions Of Prolonged Icu Staymentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study compared the long-term survival of cardiac surgery patients whose ICU stay was > 3 days with those whose stay was ≤ 3 days, and showed that survival was significantly lower in the prolonged ICU stay group (66% versus 91%). Another study by Isgro et al 25 compared 5-year survival in cardiac surgery patients whose ICU stay was either > 5 days or ≤ 5 days, and showed a significantly decreased survival rate in the patients with a longer ICU stay (43% versus 78%, respectively). Bashour et al 4 followed 142 patients for periods of 1 and 2 years after an ICU stay ≥ 10 days and noted survival rates of 45% and 38%, respectively.…”
Section: Discussionmentioning
confidence: 99%